Reducing Cycle Time in the Manufacturing Process of Circular Pattern Interpolar Products (CPIP) Using Special Fixtures on a 3-Axis CNC Machine - Sonjaya, Muhammad Luthfi; Massaguni, Massriyady; Amaluddin, Muh. Nurul Haq (INTEK: Jurnal Penelitian, 2023)
This research focuses on the design of fixture aids to support the manufacturing process of Circular Pattern Interpolation Products (CPIP), such as disk brake components, flanges, turbine disk runners, and other plate components with circular feeding patterns in the 3-Axis CNC machining process. The objective of this study is to achieve more efficient CPIP production times on 3-Axis CNC machines. The research methodology employed a design and build approach, involving the design of fixture aids, fabrication, and testing during the production of turbine disk runners on a 3-Axis CNC machine. This was done by comparing the initial workpiece setup time and the workpiece clamping transfer time using CPIP production aids versus not using CPIP production aids. The results showed that the designed CPIP Fixture significantly reduced the CPIP manufacturing Cycle Time, with a reduction of 63.11% in the initial workpiece setup time and 83.55% during the clamping transfer process.